A numerical study on the role of geometry confinement and fluid flow in colloidal self-assembly - Fang, Hongfei; Tade, Moses; Li, Qin (Elsevier, 2011)
As a strategy of autonomously organising nanoparticles into patterns or structures, colloidal self-assembly has attracted significant interests in both fundamental research and applied science. Discrete element method (DEM) coupled with a simplified fluid flow model is applied to investigate convective colloidal selfassembly. The model developed takes into account the interparticle interactions, i.e. the electrostatic repulsion, van der Waals attraction, Brownian motions, and the hydrodynamic effect. Therefore, a detailed insight of the combined influences of fluid flow field, geometrical confinement, and the interparticle interactions on the self-assembly process can be obtained. In this study, we simulated different self-assembled structures and various transition areas where a growing crystal transits from n to n+1 layer as a function of varied 3 phase contact angle, which is represented by a wedge geometry, and the velocity and direction of fluid flow. The crystal defects and the formation mechanism of different defects are theoretically studied through numericalsimulation.